2021
DOI: 10.3892/mmr.2021.11885
|View full text |Cite
|
Sign up to set email alerts
|

GINS2 affects cell proliferation, apoptosis, migration and invasion in thyroid cancer via regulating MAPK signaling pathway

Abstract: Globally, thyroid cancer (TC) is considered to be the commonest endocrine malignancy. GINS complex subunit 2 (GINS2) belongs to the GINS complex family and is associated with cellular migration, invasion and growth. The present study aimed to investigate the underlying mechanisms of GINS2 on cell viability, migration and invasion in TC cells. By using MTT, wound healing and Transwell assays, the cell viability, migration and invasion were determined. Apoptosis was examined by immunofluorescence. Western blotti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 39 publications
0
8
0
Order By: Relevance
“…The results show that GINS2 expression is increased in most tumors compared to normal tissues and correlates with various clinicopathological features. It has been demonstrated that GINS2 is expressed at higher levels in tumor tissue than in adjacent normal tissue, such as in CC[ 3 ], gastric adenocarcinoma[ 6 ], glioma[ 7 ], NSCLC[ 8 , 9 ], pancreatic cancer[ 10 , 11 ], and thyroid cancer (TC)[ 12 , 13 ]. Specifically, analysis of potential correlations between GINS2 expression levels and clinicopathological features has indicated that high GINS2 expression levels are closely associated with tumor size[ 6 , 10 ], tumor nodal metastasis (TNM) stage[ 6 , 8 ], pathological grade[ 7 ] and vascular permeation[ 10 ].…”
Section: Expression Profiles Of Gins2 In Cancersmentioning
confidence: 99%
See 2 more Smart Citations
“…The results show that GINS2 expression is increased in most tumors compared to normal tissues and correlates with various clinicopathological features. It has been demonstrated that GINS2 is expressed at higher levels in tumor tissue than in adjacent normal tissue, such as in CC[ 3 ], gastric adenocarcinoma[ 6 ], glioma[ 7 ], NSCLC[ 8 , 9 ], pancreatic cancer[ 10 , 11 ], and thyroid cancer (TC)[ 12 , 13 ]. Specifically, analysis of potential correlations between GINS2 expression levels and clinicopathological features has indicated that high GINS2 expression levels are closely associated with tumor size[ 6 , 10 ], tumor nodal metastasis (TNM) stage[ 6 , 8 ], pathological grade[ 7 ] and vascular permeation[ 10 ].…”
Section: Expression Profiles Of Gins2 In Cancersmentioning
confidence: 99%
“…In most tumors, elevated levels of GINS2 expression can increase malignant features such as tumor cell proliferation[ 3 - 7 ], migration[ 8 , 13 , 14 ], invasion[ 8 , 13 ], epithelial-mesenchymal transition (EMT)[ 8 , 10 ], anti-apoptosis effects[ 12 - 16 ] and cell cycle arrest[ 7 , 9 , 11 , 12 ], as shown in Figure 2 , which are related to the many mechanisms GINS2 is involved in, as shown in Figure 3 and Table 2 .…”
Section: Molecular Pathways Involved In Gins2mentioning
confidence: 99%
See 1 more Smart Citation
“…Accumulated evidence reports that the MAPK pathway is activated in TC and is involved in tumor immune escape 24,25,41 . Through KEGG pathway enrichment analysis, it was found that DEGs were primarily enriched in the MAPK pathway.…”
Section: Discussionmentioning
confidence: 97%
“…33 GINS2 interference attenuated cell viability, migration, and invasion in TC cell lines by inhibiting proteins in the MAPK signaling pathway, including JNK, ERK, and P38. 34 Mechanistically, pleiotrophin (Ptn) mediated insomnia-induced cognitive impairment via the MAPK signaling pathway. 35 And the MAPK pathway mediated piR-YBX1, a novel PIWIinteracting RNA, induced proliferation and metastasis of TNBC.…”
Section: Discussionmentioning
confidence: 99%